Model of smart key apportion system - Mohammad Nazreen, Jamaluddin (2007)
Model of Smart Key Apportion System is used to keep keys safely and retrieve it to its rightful owner when it is needed. It uses computer interfaced to an acquisition card, Advantech PCI-1710 which control the movement of the motor inside the machine. This project is developed from the idea of distributed control system to precisely control motors using computer. Microsoft Visual Basic is used to develop the interface and communication between computer, Advantech PCI-1710 card and the machine. Basically the operation of this project is adopting the canned drinks vendor machine which drinks will be deliver after input (money + types of drinks) given. But in this project, it is focusing on two main functions which are to return the keys when requested and keep the key back to the machine. The consumers just have to insert their unique ID number and verify it with password. Then the machine will do proper the operation accordingly.